2020
DOI: 10.1177/0846537120903692
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Image-Guided Biopsy of the Spleen: Experience at a Single Tertiary Care Center

Abstract: Purpose: The purpose of this study is to assess the complication rate of percutaneous image-guided biopsy of the spleen at our institution and to evaluate for variables associated with complication rate. Methods: This is a Research Ethics Board approved retrospective study of consecutive patients who underwent image-guided biopsy of the spleen at our institution from January 2010 to November 2019. Complications, imaging findings, and pathologic diagnosis were reviewed. Complications (major and minor) were clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Therefore, a surgical procedure would be unnecessary and will not treat systemic disease. Because of the high blood flow to the spleen, biopsy used to be rather uncommon due to the inherent high risk of bleeding, with studies reporting a high rate of complications [6,7]. But as an operation with splenectomy is also not without its risks, it can be an advantage to perform a percutaneous biopsy and spare patients a splenectomy [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a surgical procedure would be unnecessary and will not treat systemic disease. Because of the high blood flow to the spleen, biopsy used to be rather uncommon due to the inherent high risk of bleeding, with studies reporting a high rate of complications [6,7]. But as an operation with splenectomy is also not without its risks, it can be an advantage to perform a percutaneous biopsy and spare patients a splenectomy [8].…”
Section: Introductionmentioning
confidence: 99%
“…There are many diseases of the spleen, including nonneoplastic, benign neoplastic, and malignant lesions. [1] Splenic lesions of non-Hodgkin and Hodgkin lymphomas are found in 30% to 40% of patients with lymphoma. [2] Splenic metastases of solid tumors are clinically rare, although studies in autopsy cases have reported splenic metastases in 1.6% to 30% of cases.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Imaging using ultrasound (US), computed tomography (CT), and magnetic resonance can help in understanding lesion characteristics. [1] However, although advances in imaging have improved the sensitivity of lesion detection, specificity does not appear to have improved. For example, the accuracy Medicine of imaging for lymphomatous lesions in the spleen is 58% to 65%.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, diagnostic splenectomy is reserved for cases where other methods fail to identify a specific entity [ 5 , 6 ]. Splenic biopsies, although feasible, carry the risk of hemorrhage and may not always be representative [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%